Pembuatan Alat Peraga Untuk Menunjang Pembelajaran Praktikum Perancangan Proses Manufaktur - Setiawan, Indra; Asrya Sadewa, Eduardus Dimas; Yuselin, Nensi; Abikusna, Setia; Budiarti, Anisa (Universitas Teuku Umar, 2024)
The current condition, learning media in Manufacturing Process Design practicum still lacks teaching aids so that it cannot adjust its output according to industry needs. This needs to be improved to support industry-based learning. Before implementing teaching aids, the learning process was theoretical and did not involve students in real simulations, so their understanding of the manufacturing workflow was limited. This study aims to design and implement teaching aids in Manufacturing Process Design and Assembling practicums to support learning with the Learning Factory approach. The design of the teaching aids begins with observing the existing conditions, then determining the improvement plan through focus group discussions. After that, the design is carried out according to the needs of the practicum. The teaching aids made use a Programmable Logic Controller consisting of 4 stations. The use of designed teaching aids provides students with direct experience in the design and assembly process, and facilitates more interactive learning. The results of the study showed a significant increase in students' understanding of the manufacturing process, with more active involvement and an increase in the quality of assignments and practicum reports. These teaching aids have proven effective in creating a learning environment that is closer to real industrial conditions, so that they can improve students' competence in understanding manufacturing and assembly processes comprehensively.